Housing, urban governance and anti-social behaviour : Perspectives, policy and practice - Flint, John (Book collections on Project MUSE., 2006)
This book is the first comprehensive volume exploring an issue of growing importance to policy makers, academics, housing practitioners and students. It brings together contributions from the most prominent scholars in the field to provide a range of theoretical perspectives, critical analysis and empirical research findings about the role of housing and urban governance in addressing anti-social behaviour.